(untitled) (Journal of Agriculture and Environment, 2015)
Transplanting is widely practiced methods of rice establishment in puddled soils require large amount of labor and water, which are becoming scarce and expensive in Nepal. A field survey was carried out in six districts of terai region of Nepal during 2010. Sixty farmers, ten from each district were randomly selected. They were interviewed using face-to-face method based on semi-structured questionnaires to know their perception towards constraints, and economics of dry direct seeded rice (DDSR). Farmers were mostly using transplanted rice (TPR) because of less weed infestation and better crop establishment, but they were concerned with high cost of cultivation, higher water requirement and deterioration of soil after puddling operation. Farmers perceived DDSR as a cost reducing and less water requiring technology whereas severe weed infestation, poor crop establishment and reduced grain and straw yield were the major nuisance. Nevertheless, the B:C ratio of DDSR (2.0) was found higher than TPR (1.63). Therefore, DDSR could be an alternative to TPR in reducing cost of cultivation; however weeds are serious problems.